Golden eagle in the cognition of Kazakh people: Ethnographic and ethnolinguistic analysis - Kuanyshbek Kenzhalin, Aigerim Kussainova, Magripa Yeskeyeva, Sharip Amantay, Urzada Mussabekova, (Opción, 2019)
In our research article, we will study ethnographic and ethnolinguistic concepts about the golden eagle (burkit), which has a special place in the world's knowledge of Kazakh people via comparative qualitative research methods. As a result, the article analyzes the ethnographic concepts and connotations related to the golden eagle, which is one of the seven treasures, and has been given an explanation of the language units, folklore heritage. In conclusion, the development of Kazakh national sports is not only the development of sports, but also the fullness of the essence of nations.